محددات سرعة دوران النقود في سورية - اسماعيل, رولا; حسن, حسين (Latakia University Journal - Economic and Legal Sciences Series, 2018)
تهدف هذه الدراسة إلى التعريف بأهمّ المتغيّرات الاقتصادية الكلية، والتي تسبّبُ انحرافاتٍ كبيرةً أو صغيرةً في سرعة دوران النّقود (بتعريفها الواسع) في سورية. إنّ سرعة دوران النّقود تعد أحدَ أكثر المتغيّرات المُستخدمة من قبل السلطات النقدية من أجل وضع حدٍّ آمنٍ للنّموِّ النّقديِّ، وصياغة سياسة نقدية حذرة. في الحقيقة إنّ التّغيّر في سرعة دوران النّقود يَظهَرُ بشكلٍ أكبرَ على المدى الطويل, لكن له موقعٌ أساسيٌّ في السياسة النقدية. ولذلك فإن هناك قلقاً لدى السلطات النقدية في الحصول على معلومات واقعية ( صحيحة) حول المتغيّرات الاقتصادية الكلية والتي لها أثر على التَّغيُّرِ في سرعة دوران النّقود. إنّ هذه الدراسة تبحث في سبيل تحقيق هذا الهدف، فهي تُقِّدمُ فرصة لاختبار طبيعة العلاقة الدَّالِّية بين سرعة دوران النّقود ومحدِّداتها الاقتصاديَّة الكلية. تحقيقاً لهذه الغاية، استخدمت الدِّراسة سلاسل زمنيّة سنويّة خلال الفترة الممتدّة من 1990 إلى 2010. تشمل الدراسة القياسية اختبار استقرارية السّلاسل الزّمنيّة من خلال تطبيق اختبار ديكي فولر الموسَّع (ADF)، وتقديم النموذج والكشف عن وجود تكامل مُشترك باستخدام منهج الحدود بين سرعة دوران النقّود V2 وأهمِّ المُتغيِّرات الاقتصادية الكلية، وتقدير العلاقة في المدى القصير والمدى الطويل باستخدام نموذج الانحدار الذاتيّ للفجوات الزمنية الموزّعة المُتباطِئة (ARDL). تؤكدالدراسة وجود علاقة طردية بين سرعة دوران النّقود، و النمو في نصيب الفرد من الدخل، وهذه النتيجة تدعم النظرية الكمية في النّقود، إنّ كّلً من سعر الصرف الحقيقي، و مُعّدل النموّ السكاني و درجة النقدية في الاقتصاد ترتبط مع سرعة دوران النّقود بعلاقة عكسية على المدى القصير والطويل، بالنسبة للمتغير المُمَثّل للتطور بالقطاع المصرفي- نسبة الائتمان المحلي المقدم للقطاع الخاص إلى الناتج المحلي الإجمالي- فقد أظهر علاقة إيجابية على المدى القصير، لكن هذه العلاقة تصبح عكسية على المدى الطويل، وبالنسبة لمعدل التّضخّم فقد أظهر علاقة عكسية على المدى القصير لكن هذه العلاقة تصبح غير معنوية على المدى الطويل. وتظهر النتائج تأثر سرعة دوران النّقود بشكل سلبي بكل من معدل التّضخّم ومعدل النمو السكاني، وهذا يعود لمحدودية الموارد في البلد، حيث أنّ الزيادة في مستوى الأسعار وزيادة السكان، تخفض من سرعة دوران النّقود -التي تكون قيمتها الشرائية أقل من قبل-، وذلك بتخفيض الإنفاق على العناصر غير الضرورية وتغيير الأفراد لنمط استهلاكهم، وعلى الرغم من التوقع بأن ارتفاع الأسعار ستسبب زيادة في سرعة دوران النّقود إلا أنَّ محدودية الموارد والدخل جعلت هذه العلاقة عكسية، وتظهر النتائج بأن السلطات النقدية لا يمكن أنّ تضمن رافعة مالية بإصدار المزيد من النّقود بدون التسبب بضغوط تضخّمية. This study attempts to identify the significant macroeconomic variables that are considered to generate larger or smaller variation in the velocity of money (VM) in Syria. The VM is one of the most widely used variables by the monetary authority to estimate the safe limit of monetary growth and to formulate a careful monetary policy. It is true that the change of velocity of money is rather a long run occurrence, but it has a central place in monetary policy. It is therefore a matter of concern for monetary authorities to have reliable information about macroeconomic variables that have impact on variation of velocity. This study supplies an investigation in order to attain this goal. It provides chance to examine the nature of the functional relationship between the velocity and its macroeconomic determinants. To this end, the study utilized annual time series data set over the period 1990 to 2010. Econometric techniques include testing the stationary of data by applying (ADF) test and applying Autoregressive Distributed Lag (ARDL) method of estimation. Moreover, Short run and long run estimates were found. The paper confirms a positive and statistically significant relationship between the growth of per capita income and the velocity of money, which supports the quantity theory of money. The real exchange rate, rate of population growth and the degree of monetization in economy have negative relation with velocity of money in short and long run. The banking sector development variable adopted, Domestic credit to private sector % of GDP, has a positive relationship with the income velocity of money in the short run, but this relationship becomes negative in the long run. The inflation rate has a negative relationship with the income velocity of money in the short run, but this relationship becomes in significant in the long run. The income velocity of money is appeared to be inversely influenced by population and inflation rate. One may have an idea that given the limited resources of this region, whenever population and price level will increase, it reduces income velocity of money having lesser purchasing power as past, by cutting their expenditure on unnecessary items, keeping standard of living changed, and also by changing their consumption pattern. Price level of country should be cause of higher income velocity of money but due to limited resources and income of this region, it has reverse effects. The results show that the monetary authority cannot obtain additional leverage by issuing more money without generating high inflationary pressure.